Understanding saproxylic beetles: new records of Tetratomidae, Melandryidae, Synchroidae, and Scraptiidae from the Maritime Provinces of Canada (Coleoptera: Tenebrionoidea) - Majka, Christopher G.; Pollock, Darren A. (Zootaxa, 2006)
New species records for Tetratomidae, Melandryidae, Synchroidae, and Scraptiidae from the Maritime Provinces of Canada are given. Known bionomics of these saproxylic species are summarized and new bionomic observations are provided. Twenty-five species are newly recorded from Nova Scotia, 10 from Prince Edward Island, and three from New Brunswick. Thirty-seven species are now known from the region, a substantial increase from the 23 species known hitherto. Range extensions for 19 species are noted. The composition of the region’s fauna is briefly discussed, focusing on a disparity in the collection efforts between provinces, and also on island faunas. Finally the fauna is examined in the context of a developing knowledge of saproxylic beetles in Nova Scotia, along with potential concerns about the impact that forest management practices.